Clinical Characteristics and Outcomes of Adults With a History of Heart Failure Hospitalized for COVID-19. (14th September 2021) - Goyal, Parag; Reshetnyak, Evgeniya; Khan, Sadiya; Musse, Mahad; Navi, Babak B.; Kim, Jiwon; Allen, Larry A.; Banerjee, Samprit; Elkind, Mitchell S.V.; Shah, Sanjiv J.; Yancy, Clyde; Michos, Erin D.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: It is important to understand the risk for in-hospital mortality of adults hospitalized with acute coronavirus disease 2019 (COVID-19) infection with a history of heart failure (HF). Methods: We examined patients hospitalized with COVID-19 infection from January 1, 2020 to July 22, 2020, from 88 centers across the US participating in the American Heart Association's COVID-19 Cardiovascular Disease registry. The primary exposure was history of HF and the primary outcome was in-hospital mortality. To examine the association between history of HF and in-hospital mortality, we conducted multivariable modified Poisson regression models that included sociodemographics and comorbid conditions. We also examined HF subtypes based on left ventricular ejection fraction in the prior year, when available. Results: Among 8920 patients hospitalized with COVID-19, mean age was 61.4±17.5 years and 55.5% were men. History of HF was present in 979 (11%) patients. In-hospital mortality occurred in 31.6% of patients with history of HF, and 16.9% in patients without a history of HF. In a fully adjusted model, history of HF was associated with increased risk for in-hospital mortality (relative risk: 1.16 [95% CI, 1.03–1.30]). Among 335 patients with left ventricular ejection fraction, heart failure with reduced ejection fraction was significantly associated with in-hospital mortality in a fully adjusted model (heart failure with reduced ejection fraction relative risk: 1.40 [95% CI, 1.10–1.79]; heart failure with mid-range ejection fraction relative risk: 1.06 [95% CI, 0.65–1.73]; heart failure with preserved ejection fraction relative risk, 1.06 [95% CI, 0.84–1.33]). Conclusions: Risk for in-hospital mortality was substantial among adults with history of HF, in large part due to age and comorbid conditions. History of heart failure with reduced ejection fraction may confer especially elevated risk. This population thus merits prioritization for the COVID-19 vaccine.